2013
DOI: 10.1002/pd.4100
|View full text |Cite
|
Sign up to set email alerts
|

Discordant noninvasive prenatal testing results in a patient subsequently diagnosed with metastatic disease

Abstract: What's already known about this topic? Noninvasive prenatal testing for detection of trisomies 21, 18, and 13 is clinically available and is reported to have a false positive rate of 1% or less This technology utilizes massively parallel shotgun sequencing of cell‐free DNA, of maternal and placental origin, present in maternal plasma What does this study add? Unexplained abnormal noninvasive prenatal testing results should prompt consideration of a maternal source of the abnormal cell‐free DNA, such as malig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
169
1
4

Year Published

2013
2013
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 194 publications
(178 citation statements)
references
References 7 publications
3
169
1
4
Order By: Relevance
“…This abnormal NIPT result was thought to be due to the multiple cytogenetic abnormalities found in the tumor. 9 Of patients with "unclassified" NIPT results, one fetus had confirmed trisomy 18 and two had second-trimester fetal demises without postmortem genetic testing ( Table 2). Two patients delivered term infants with normal newborn examinations ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This abnormal NIPT result was thought to be due to the multiple cytogenetic abnormalities found in the tumor. 9 Of patients with "unclassified" NIPT results, one fetus had confirmed trisomy 18 and two had second-trimester fetal demises without postmortem genetic testing ( Table 2). Two patients delivered term infants with normal newborn examinations ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…One falsepositive result for monosomy 18/trisomy 13 in a patient with Original research article a subsequent postnatal diagnosis of maternal cancer was observed. 9 There was also, one false negative for trisomy 18 in a patient with an "unclassified" result for trisomy 13, but no aneuploidy was detected for trisomy 18 on NIPT. Mennuti et al 18 recently published eight cases with discordant results between NIPT results and cytogenetic testing of the pregnancy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several reported cases, followup amniocentesis based on positive cfDNA screening results has identified a normal karyotype, suggesting a false positive cfDNA screening result [3][4][5][6][7][8]. Even though the published data indicates high sensitivity (≥99% for trisomy 21, ≥92% for trisomy 18, and ≥87% for trisomy 13) and specificity (≥99% for trisomy 21, 18, and 13) for aneuploidy detection [9], false positive results have been reported for confined placental mosaicism, vanishing twin or cotwin demise, fetal chromosome rearrangement, and maternal chromosome abnormalities or malignancy [10][11][12][13][14]. Based on several reports, false negative results for fetal aneuploidy are much less common than false positive results [4-6, 15, 16].…”
Section: Introductionmentioning
confidence: 97%
“…Third, CVS and AC are exclusive methods for the detection of fetal conditions and allow non-disclosure testing for inherited or acquired diseases of the prospective mother, e.g. Huntington disease or maternal malignancies [59]. Incidental maternal findings can be avoided completely if a maternal contamination is excluded in the sampled material.…”
Section: Invasive Prenatal Diagnostics In a Nipt Contextmentioning
confidence: 99%